Feminist Success Stories - Célébrons nos réussites féministes - Karen A. Blackford (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 1999)
Abuses by international corporations, withdrawal of social services and implementation of regressive legislation continue to impoverish women and reduce the quality of their everyday lives: women have reason to be demoralized. Recognizing this challenging and difficult situation, this volume reviews women's successes at feminizing Canadian institutions. It is intended to hearten the women's movement, and show the potential for feminist change and suggest ways to realize this potential.